2021
DOI: 10.1038/s41598-021-00421-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling of Burkholderia cenocepacia in synthetic cystic fibrosis sputum medium reveals nutrient environment-specific production of virulence factors

Abstract: Infections by Burkholderia cenocepacia lead to life-threatening disease in immunocompromised individuals, including those living with cystic fibrosis (CF). While genetic variation in various B. cenocepacia strains has been reported, it remains unclear how the chemical environment of CF lung influences the production of small molecule virulence factors by these strains. Here we compare metabolomes of three clinical B. cenocepacia strains in synthetic CF sputum medium (SCFM2) and in a routine laboratory medium (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 126 publications
1
21
0
Order By: Relevance
“…Our lab has previously shown that sublethal concentrations of trimethoprim induce a strain-specific response in the K56-2 strain not seen in other B. cenocepacia strains, resulting in increased production of secondary metabolites such as fragin and pyrazine- N -oxides. 12, 13 Plotting PC1 against PC3 revealed an additional trend where samples from pigmented strains show separation from those of non-pigmented strains along PC3 (10.9% of the total variance explained) (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our lab has previously shown that sublethal concentrations of trimethoprim induce a strain-specific response in the K56-2 strain not seen in other B. cenocepacia strains, resulting in increased production of secondary metabolites such as fragin and pyrazine- N -oxides. 12, 13 Plotting PC1 against PC3 revealed an additional trend where samples from pigmented strains show separation from those of non-pigmented strains along PC3 (10.9% of the total variance explained) (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Culturing was performed in the presence of antibiotic trimethoprim since it is a known inducer of secondary metabolites produced by B. cenocepacia K56-2 and also undergoes biochemical modification by pigmented B. cenocepacia , while also being the first line of defense again B. cenocepacia infections. 12, 13 To enhance extraction of chemically diverse metabolites, liquid-liquid and solid-phase extractions were performed. These extracts were pooled together prior to UHPLC-HRMS/MS analysis in positive and negative ionization modes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations